Pengaruh Tinggi dan Diameter Cerobong Pltu Terhadap Dispersi SO2 Di Udara Menggunakan Model Gaussian Plume - Nur Jannah Baturante; Nurbaiti Kumendong (Jurnal Pendidikan Kimia Unkhair (JPKU), 2022)
AbstractGaussian plume model was used to model the SO2 dispersion of 1000 MW coal power plant. This study used two scenarios to figure out the effect of pollutant source physical condition height and diameter of stack to SO2 dispersion which result from coal burning in power plant. The result showed that the increase of sulfur in coal increase ground level concentration of SO2. Decreased of atmospheric stability, caused the increase of SO2 ground level concentration that closer to the pollutant source. Height and diameter of stack, showed similar effect. Sulfur dioxide ground level concentration decrease and occured closer to the pollutant source, caused by  the increase of those parameters. The lowest SO2 ground level concentration resulted from high stack 275 m, with MGLCs 106,55 μg/m3, and diameter 8,75 m; with MGLCs 112,15 μg/m3, which has exceeded the threshold and gave negative effects on human and the environment.Kata Kunci :        Gaussian Plume, Coal power plant, Dispersion model, SO2 concentration